A randomised pilot study comparing 13 G vacuum-assisted biopsy and conventional 14 G core needle biopsy of axillary lymph nodes in women with breast cancer. Issue 6 (June 2016) - Maxwell, A.J.; Bundred, N.J.; Harvey, J.; Hunt, R.; Morris, J.; Lim, Y.Y.
Abstract : Aim: To compare the acceptability, safety, and feasibility of vacuum-assisted biopsy (VAB) and core needle biopsy (CNB) of axillary lymph nodes in women with breast cancer. Materials and methods: This parallel, non-blinded, randomised study was approved by the National Research Ethics Service. Following written informed consent, women with abnormal appearing axillary lymph nodes and radiologically malignant breast masses were randomised 1:1 to lymph node sampling under local anaesthetic with either 14 G CNB or 13 G VAB in a single UK centre. Primary outcomes were study uptake rate and patient willingness to undergo a repeat procedure if necessary. Procedure duration, immediate and post-procedure pain scores, diagnostic yield, complications, and surgical histopathology were recorded. Results: Ninety-five women were approached; 81 (85.3%) consented and were randomised. Forty underwent CNB; 40 underwent VAB; one was excluded. Median age was 57 years. The median procedure time was 2 minutes for both techniques. The median number of samples obtained was three for CNB and four for VAB. Median pain scores for the procedure and first 3 days were 1/10 and 1/10 for CNB and 1/10 and 2/10 for VAB ( p =0.11 and 0.04). More women were prepared to undergo repeat CNB compared to VAB, but the difference was not significant (38/39 versus 33/39; p =0.11). Two patients developed a haematoma after VAB. One CNB and six VABs failed to yield adequate tissue ( p =0.11), but the sensitivity was similar at 79% and 78%. Conclusion: Study uptake was high. Acceptability of the two procedures was similar, but VAB was associated with more post-procedure pain. The sensitivity appears to be similar. Highlights: Vacuum biopsy of axillary lymph nodes can be performed rapidly. Post-procedure pain was slightly higher in women who underwent vacuum biopsy. The inadequate yield rate of vacuum biopsy may be higher than that for core biopsy. Sensitivity of 13-gauge vacuum biopsy and 14-gauge core biopsy appear similar. There is insufficient evidence for axillary lymph node VAB in routine practice.